Internationalization of Countering Dishonest Tax Practices - Matras, Tomasz (Historia i Polityka, 2022)
According to the estimates from 2013, 8 per cent of the global capital was located in the so-called ‘offshore zones’, or jurisdictions used for tax optimization, which was $7.6 trillion at the time. Locating funds in tax havens resulted in a reduction of revenue in the relevant jurisdictions of between $500 billion and $600 billion per year. International community has recognized the need to adopt international regulations to counteract the erosion of the tax base. For this purpose, the Common Reporting Standard (CRS) was adopted in 2014. The main idea behind implemented changes was to have an effective exchange of financial information between national tax authorities. This article provides information on the reasons for the adoption of the standard in 2014 and the practice of financial information exchange after 2017. Additionally, data on the effectiveness of exchange of information and critical analysis of some aspects of the functioning of the CRS were presented. The assumptions of the article are presented in terms of internationalization, given the fact that counteracting dishonest taxpayers has shifted from the national to the international level in recent years.